Arthroscopy of the Elbow in Dogs - Bardet, J. F. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The technique of arthroscopy of the elbow joint using the craniolateral portal is described in dogs. The technique was developed on ten cadavers and six experimental dogs. It allows a direct visualization of the cranial bony structures of the elbow of the cranial recess as well as of the humeroulnar joint and anconeal process through the supratrochlear foramen. The technique appears safe and reliable. Postoperative neurovascular injuries were not observed.The technique of arthroscopy of the elbow joint using the craniolateral portal is described in dogs.
Keywords: Arthroscopy; elbow joint; dog